2019
DOI: 10.1177/1937586719851271
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptions of Nurses About the Behavioral Needs for Daylighting and View to the Outside in Inpatient Facilities

Abstract: Objectives: This research aims to explore the perceptions of nursing staff regarding the effects of daylighting on behavioral factors including mood, stress, satisfaction, medical error, and efficiency. Background: In spite of an extensive body of literature seeking to investigate the impact of daylighting on patients, a limited number of studies have been done for the sake of nurses’ perceptions and behavioral responses. Method: A mixed-methods approach, comprised of qualitative explorations (structured inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
(41 reference statements)
0
15
0
Order By: Relevance
“…As the primary environmental cue for the body’s master biological clock, light has been shown to impact sleep, mood, performance, alertness, quality of life, and overall health in various populations [ 4 , 5 ]. Optimizing light for the promotion of circadian alignment in architectural settings involves ensuring the proper levels, timing, duration, and spectra of light that occupants are exposed to throughout the day while minimizing their exposure during the evening, prior to bedtime.…”
Section: Introductionmentioning
confidence: 99%
“…As the primary environmental cue for the body’s master biological clock, light has been shown to impact sleep, mood, performance, alertness, quality of life, and overall health in various populations [ 4 , 5 ]. Optimizing light for the promotion of circadian alignment in architectural settings involves ensuring the proper levels, timing, duration, and spectra of light that occupants are exposed to throughout the day while minimizing their exposure during the evening, prior to bedtime.…”
Section: Introductionmentioning
confidence: 99%
“…Other research suggested that patient satisfaction was independent of the window size and shape [8]. In a follow-up study, Gharaveis et al (2020) interviewed care providers in an ICU and found that staff preferred larger windows in the unit to allow more daylight into the patient rooms and to provide better views to the outside for the patient [15].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical staff has also reflected on these patient desires, reporting that patients likely prefer to have windows next to their bed to have a view outside, but not in direct sunlight. In this study, more than half of the participants thought having a window in front of the bed or near the foot of the bed would be most effective [15]. Additionally, one study found that patients were challenged by poorly positioned windows and could not maintain a connection with the outside [14].…”
Section: Introductionmentioning
confidence: 99%
“…In a healthcare setting, natural light, fresh air, and views on of green space could effectively reduce the psychological fatigue of the patients and staffs due to restoration of nature, in both visual and physical contact ( 9 , 26 , 32 ). Introducing daylighting by arranging window toward natural and green resources could reduce the fatigue and stress of the occupants by enhancing their satisfaction, mood, and alertness ( 33 , 34 ). Though the knowledge from a spatial perspective was limited, some studies still revealed that environmental factors such as functional layout, interior exterior, and environmental features were associated with the fatigue in the various setting ( 27 , 29 ).…”
Section: Introductionmentioning
confidence: 99%